Про переваги демократії - Полозова, О. О. (ХНУРЕ, 2023)
We are currently in a war against the dictatorship of rashism for democratic values, for our freedom and rights. Sociological studies confirm that Ukrainians want to live in a democratic country. However, in the conditions of war, the problem of internal risks of the development of authoritarianism is also actualized. Therefore, understanding the essence of democracy is of fundamental importance for us. The purpose of this study is to analyze the features and advantages of a democratic form of government, in particular, in comparison with a dictatorship.